2019
DOI: 10.5114/jcb.2019.84503
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study for CT-guided 125 I seed implantation assisted by 3D printing coplanar and non-coplanar template in peripheral lung cancer

Abstract: Purpose We compared the three-dimensional printed non-coplanar template (3DPNCT) plans with 3D-printed coplanar template (3DPCT) plans for radioactive seed implantation (RSI) in lung cancer and explored the differences between the two technologies. Material and methods 33 patients with peripheral lung cancer that received 3DPCT-assisted RSI in our department between June 2017 and February 2018 were analyzed. A 3DPNCT plan was re-designed for all patients. The prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
(18 reference statements)
3
29
0
Order By: Relevance
“…were not statistically different from the preoperative plan. Considering that is related with the seed implantation under template control, as it decrease the bleeding and relative motion, therefore it can guarantee the precise control of target dose on the basis of better control of tumor target volume, this is consistent with the recent literature reports [13,14].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…were not statistically different from the preoperative plan. Considering that is related with the seed implantation under template control, as it decrease the bleeding and relative motion, therefore it can guarantee the precise control of target dose on the basis of better control of tumor target volume, this is consistent with the recent literature reports [13,14].…”
Section: Discussionsupporting
confidence: 88%
“…No patients were given systemic chemotherapy and other treatments from seed implantation to followup deadline. The analysis of prognostic factors in this study also suggested that tumor location and disease types are the influencing factors affecting CT-guided 3D template-assisted 125 I particle implantation techniques, and factors such as template types are not the factors that affecting prognosis [13].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…No patients were administered systemic chemotherapy or other treatments from seed implantation to the completion of follow-up. The analysis of prognostic factors in this study also suggested that the tumour site and type are influential factors for CT-guided 3D template-assisted 125 I particle implantation technology, and other factors, such as template type, are not factors that affect prognosis [13].…”
Section: Discussionmentioning
confidence: 52%
“…As the product of several minimally invasive disciplines, radioactive 125 I particle implantation technology is a relatively accurate treatment in clinical practice. With the pre-operative use of the BTPS to develop a rational treatment plan and the implementation of the treatment plan intra-operatively, CT-guided 3D template-assisted 125 I seed implantation for the treatment of malignant tumours is more accurate [4,[13][14][15] and extends the survival time and quality of life of patients with advanced malignancies. Mo et al [11] applied CT-guided seed implantation combined with chemotherapy to treat metastatic soft tissue tumours after 4-6 cycles of first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%